2019
DOI: 10.3802/jgo.2019.30.e53
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaginal brachytherapy in intermediate and high-intermediate risk endometrial cancer: a multicenter study from the FRANCOGYN group

Abstract: Objective According to recent European Society of Medical Oncology, European Society of Gynaecological Oncology and European Society of Radiotherapy and Oncology guidelines, adjuvant vaginal brachytherapy (VB) is optional in patients with intermediate risk (IR) and high-intermediate risk (HIR) endometrial cancer (EC). The aim of this French retrospective, multicenter study was to assess the impact of VB in these groups on local recurrence rate, local recurrence-free survival (RFS) and overall surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…At 15 years, locoregional recurrence rate was reported as 5.8% in external beam radiotherapy (EBRT) arm and 15.5% in follow-up arm (p < 0.001). In this trial, since the authors reported that vagina was the most frequent site of recurrence in 75% patients undergoing surgery alone [19], they concluded that vaginal brachytherapy (VBT) alone is effective treatment to obtain vaginal control avoiding PORT-related complications [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…At 15 years, locoregional recurrence rate was reported as 5.8% in external beam radiotherapy (EBRT) arm and 15.5% in follow-up arm (p < 0.001). In this trial, since the authors reported that vagina was the most frequent site of recurrence in 75% patients undergoing surgery alone [19], they concluded that vaginal brachytherapy (VBT) alone is effective treatment to obtain vaginal control avoiding PORT-related complications [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%